Eurozone: Original laws, present problems and challenges for the future - Marcello Minenna (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
The European monetary union was born as a result of a negotiation process among the founding countries profoundly influenced by the economic and political dynamics of the '90s: the experience of the EMS, the German unification process, the desire of France to prevent the reaffirmation of German supremacy in the European continent, the need for countries like Italy to reduce the cost of servicing public debt. Despite the strong differences between the countries involved, the conviction prevailed that the German fiscal recipe could be successfully exported to neighboring States and that the centralization of monetary policy at the European Central Bank while keeping fiscal sovereignty at a national level could be achieved without trauma. The experience of the last decade shows, however, that the a monetary union with a derisory federal budget and whose central bank has exclusively an inflation target and cannot act as a lender of last resort in the Member States is endogenously predisposed to the formation of large economic-financial imbalances between the various countries and is particularly vulnerable to exogenous shocks. The reversal of the diverging dynamics still in progress - captured by the unprecedented size of the Target 2 balances of countries such as Germany and Italy - requires a profound rethinking of the European project in accordance with the principles of subsidiarity and of sustainable and shared development enshrined in the Treaties.
Keywords: E02; G01; H12; H63; 330; Target 2 balances; risk-sharing; Eurozone overhaul; zero-spread target; public debt mutualization; high-multiplier investments; cancellation of impaired debts; convergence trades; collective action clauses